Adverse roles of mast cell chymase-1 in COPD. Issue 6 (8th December 2022) - Liu, Gang; Jarnicki, Andrew G.; Paudel, Keshav R.; Lu, Wenying; Wadhwa, Ridhima; Philp, Ashleigh M.; Van Eeckhoutte, Hannelore; Marshall, Jacqueline E.; Malyla, Vamshikrishna; Katsifis, Angelica; Fricker, Michael; Hansbro, Nicole G.; et al.
Background: COPD is the third leading cause of death worldwide. Cigarette smoke (CS)-induced chronic inflammation inducing airway remodelling, emphysema and impaired lung function is the primary cause. Effective therapies are urgently needed. Human chymase (hCMA)1 and its orthologue mCMA1/mouse mast cell protease (mMCP)5 are exocytosed from activated mast cells and have adverse roles in numerous disorders, but their role in COPD is unknown. Methods: We evaluated hCMA1 levels in lung tissues of COPD patients. We used mmcp5 -deficient ( −/− ) mice to evaluate this protease's role and potential for therapeutic targeting in CS-induced experimental COPD. In addition, we used ex vivo/in vitro studies to define mechanisms. Results: The levels of hCMA1 mRNA and CMA1 + mast cells were increased in lung tissues from severe compared to early/mild COPD patients, non-COPD smokers and healthy controls. Degranulated mast cell numbers and mMCP5 protein were increased in lung tissues of wild-type mice with experimental COPD. mmcp5 −/− mice were protected against CS-induced inflammation and macrophage accumulation, airway remodelling, emphysema and impaired lung function in experimental COPD. CS extract challenge of co-cultures of mast cells from wild-type, but not mmcp5 −/− mice with wild-type lung macrophages increased in tumour necrosis factor (TNF)-α release. It also caused the release of CMA1 from human mast cells, and recombinant hCMA-1 induced TNF-α release from human macrophages. Treatment with CMA1 inhibitor potently suppressed these hallmark features of experimental COPD. Conclusion: CMA1/mMCP5 promotes the pathogenesis of COPD, in part, by inducing TNF-α expression and release from lung macrophages. Inhibiting hCMA1 may be a novel treatment for COPD. hCMA1 released from mast cells induces macrophages to release TNF-α in the lung and promotes the pathogenesis of COPD. hCMA1 may be a novel therapeutic target in COPD. https://bit.ly/3b3OkKT